Mind the gap: Improving discharge communication between secondary and primary care. Issue 1 (2nd September 2015) - Cresswell, Aynsley; Hart, Matthew; Suchanek, Ondrej; Young, Tania; Leaver, Laurence; Hibbs, Stephen
Abstract: Foundation year doctors (FYDs) write most hospital discharge communication, although they have minimal training in this skill. Poor quality discharge summaries increase the risk of adverse events and rehospitalisation. With a multidisciplinary team approach, we developed a list of "golden rules" for good discharge communication. Against these standards, we analysed the quality of electronic inpatient discharge documentation (eIDD) sent over two months from OUH Trust. We found one third of eIDDs were missing details of the discharging doctor. In 68%, changes to medications were not documented clearly and follow-up was not completed in 40%. To improve this suboptimal state, we implemented interactive teaching sessions for FYDs, designed an e-learning module, and suggested software changes to the current electronic discharge proforma. Early re-audit one month after the first teaching sessions did not demonstrate any significant improvement. However, re-auditing after twelve months is planned. Through data collection and discussion with key stakeholders, we have identified standards for discharge communication. We developed interventions to help the trust achieve these standards, aiming to enhance patient safety in the peri-discharge period. While discharge communication is delegated to less-experienced team members, they should receive clear guidance and training.